2016
DOI: 10.4088/pcc.15m01883
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Course of Persistent Delusional Disorder

Abstract: In our center, PDD appears to be uncommon and has a near-equal gender representation. Infidelity was the most common delusion, which is in contrast to the reported literature. The diagnosis of PDD appears to be stable with good response to atypical antipsychotics if compliance can be ensured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
9
0
4
Order By: Relevance
“…The general symptoms defined in ICD‐9‐CM include hallucinations, dizziness and giddiness, sleep disturbances, and so on, which are the common symptoms and complaints about delusional and anxiety disorders patients according to DSM‐5 . About 17% of the patients in delusional disorders present hallucinations; anxiety disorders patients were more likely to develop vertigo than the control patients . Among patients with anxiety disorders, the confidence of simultaneous general symptoms and sleep disturbances was high (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general symptoms defined in ICD‐9‐CM include hallucinations, dizziness and giddiness, sleep disturbances, and so on, which are the common symptoms and complaints about delusional and anxiety disorders patients according to DSM‐5 . About 17% of the patients in delusional disorders present hallucinations; anxiety disorders patients were more likely to develop vertigo than the control patients . Among patients with anxiety disorders, the confidence of simultaneous general symptoms and sleep disturbances was high (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study also found a negative relationship between digestive diseases diagnosis and mental distress. 37 These may be possibly due to the side effects for gastrointestinal diseases of antipsychotic medicine 38 About 17% of the patients in delusional disorders present hallucinations 40 ; anxiety disorders patients were more likely to develop vertigo than the control patients. 41 Among patients with anxiety disorders, the confidence of simultaneous general symptoms and sleep disturbances was high (Figure 1).…”
Section: Number Of Patients With and Number Of Patients Withmentioning
confidence: 99%
“…Die Prävalenz dieser Erkrankung liegt bei 24-30/100 000 [1]. Frauen erkranken häufiger und das Alter bei Erkrankungsbeginn liegt bei 35-55 Jahren [2]. Der Inhalt des Wahns kann geprägt sein durch Liebe, Größenwahn, Eifersucht/Sorge vor Untreue, Verfolgung oder somatische Beschwerden [3].…”
Section: Wahnhafte Störungunclassified
“…Der Inhalt des Wahns kann geprägt sein durch Liebe, Größenwahn, Eifersucht/Sorge vor Untreue, Verfolgung oder somatische Beschwerden [3]. Am häufigsten liegt ein Verfolgungswahn vor (58-64 % der Fälle), gefolgt von einem Eifersuchtswahn [2]. Affektive Symptome und Suizidalität (8-21 % der Patienten) treten gehäuft auf, wohingegen selten Halluzinationen zu verzeichnen sind [1,3].…”
Section: Wahnhafte Störungunclassified
“…We reviewed the case records of 455 patients with PDD (males: n = 236 [51.9%]; females: n = 219 [48.1%]) as part of a retrospective review published earlier. [5] We examined gender differences on age, sociodemographics, illness variables including age at the onset of illness, duration of illness, family history, clinical and treatment details, occupational functioning, number of follow-ups, and hospitalizations. For between-group comparisons, independent samples t -test was used for continuous variables and Chi-square test for categorical variables.…”
mentioning
confidence: 99%